BrIM 5D models and Lean Construction for planning work activities in reinforced concrete bridges (2017)
Integrating Building Information Modeling (BIM) and Lean Construction (LC) can improve the reinforced concrete bridging planning process, due to the possibility of managing the project information with BIM to obtain accurate input data that benefit the application of LC principles. The application of BIM to bridges is called Bridge Information Modeling (BrIM). In this paper, we study the feasibility of jointly apply BrIM technology and LC philosophy, instead of the individual use of BrIM models for planning reinforced concrete bridges. We used an investigative approach based on a case study, divided into two stages: in the first, we planned the case study with BrIM 3D models; and in the second, with BrIM 5D models and LC. The integration of BrIM and LC improve the results of the project planning stage by early detecting problems and constraints; this detection has the visualization and information management advantages provided by BIM, which along with the application of LC principles improve project planning, and encourage waste reduction.